2021
DOI: 10.1002/ijgo.13647
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of ectopic pregnancy during the COVID‐19 pandemic: A retrospective study of a collateral effect

Abstract: Objective We aimed to assess the rates of overall diagnosis of ectopic pregnancy (EP), treatment modality and associated complications during the COVID‐19 pandemic compared to the exact time period in the previous year (pre‐COVID‐19). Methods A retrospective cohort study was conducted at a single referral regional center (Shaare Zedek Medical Center, Jerusalem, Israel). Prevalence of the diagnosis of EP, treatment modality and associated complications during the COVID‐19 lockdown period in the state of Israel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 12 publications
2
27
1
2
Order By: Relevance
“…However, this hypothesis is not supported by the findings of this study. Our findings are also in contrast to those of the currently available literature on the impact of the COVID-19 pandemic on EP diagnosis and management, in which it has been suggested that hesitancy amongst patients in accessing healthcare resources led to an increase in the rates of surgery, ruptured EP, blood loss and hemodynamic instability [8][9][10][11][12][13] .…”
Section: Discussioncontrasting
confidence: 99%
“…However, this hypothesis is not supported by the findings of this study. Our findings are also in contrast to those of the currently available literature on the impact of the COVID-19 pandemic on EP diagnosis and management, in which it has been suggested that hesitancy amongst patients in accessing healthcare resources led to an increase in the rates of surgery, ruptured EP, blood loss and hemodynamic instability [8][9][10][11][12][13] .…”
Section: Discussioncontrasting
confidence: 99%
“…10 Barg et al have reported that in this pandemic of COVID-19 more women have reported after tubal rupture than before rupture thereby increasing need for emergency surgical management and blood transfusion. 11 In our hospital a policy was made to all elective deferrable surgeries were cancelled, while acute emergencies were managed. The existing health care infrastructure, which was already burdened in non-COVID period was further divided between COVID and non-COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…Included study characteristics 12 studies, involving a total of 3122 women, were eligible for data extraction (Table 1). Five studies were from Europe (UK and Italy) (3) (21) (22) (23,24), four from America (USA and Canada) Gomez (4) (6) (7) (25) and three from the Middle East (Israel) (2,26), (27) . Nine studies were single centre retrospective studies (2, 3, 6)(10) (22,23,(25)(26)(27), one was a multicentred prospective study (21) and two multicentred retrospective studies (4), (24).…”
Section: Figurementioning
confidence: 99%
“…Five studies were from Europe (UK and Italy) (3) (21) (22) (23,24), four from America (USA and Canada) Gomez (4) (6) (7) (25) and three from the Middle East (Israel) (2,26), (27) . Nine studies were single centre retrospective studies (2, 3, 6)(10) (22,23,(25)(26)(27), one was a multicentred prospective study (21) and two multicentred retrospective studies (4), (24). All studies compared a cohort of women diagnosed with an ectopic pregnancy during the first Covid wave in early 2020, with a similar cohort managed pre-Covid: 2018-2019.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation